FORMULASI STRATEGI DIVISI MERCHANT BUSINESS GROUP PT. BANK CIMB NIAGA, TBK - Faras Zulina Ayunani (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
The development of transactions in Indonesia shows good progress and almost all transactions used have been carried out non-cash. People like to use Card-Based Payment Instruments (APMK) to make transactions at merchants or stores. At the same time, the banking industry saw opportunities in the situation, so the bank also provided facilities to process card transactions. PT. Bank CIMB Niaga, Tbk as one of the acquiring banks in Indonesia must have a good strategy to deal with competition among other acquiring banks.This study aims to analyze the opportunities and threats faced by the Merchant Business division of PT. Bank CIMB Niaga, Tbk, also to show the strengths and weaknesses faced to improve the ratings of the business merchants of PT. Bank CIMB Niaga, Tbk in the acquiring industry. Next is to formulate and identify which strategies should be applied in the business merchant division of PT. Bank CIMB Niaga, Tbk.The data collection technique for this research is by conducting a study from the Merchant Business of PT. Bank CIMB Niaga, Tbk, starting from library studies and direct investigations in the field (Kueisoner, documentation and interviews). The method used for data analysis uses five porter strength analysis for external environmental analysis and porter value chain analysis for internal environment analysis. Then, from the results of internal and external analysis will be arranged into the matrix EFE and IFE. The results of internal and external analysis are combined using the SFAS (Strategic Factor Analysis Summary) matrix to select the dominant factors that significantly influence the merchant business division. For strategy formulations, the SWOT Matrix, Internal-External Matrix, and Grand Strategy matrix are used. Finally, to determine the strategy that will be implemented, the QSPM (Quantitative Strategic Planning Matrix) matrix is ??used.The results of this study indicate that there are several strategies that must be implemented within five years. In the first year, the business merchant division of PT. Bank CIMB Niaga, Tbk must run a product development strategy. In the second and third year, the market development strategy must be carried out, and in the fourth and fifth years must carry out market penetration strategies.